Building Climate-Smart Villages: Five approaches for helping farmers adapt to climate change - International Crops Research Institute for the Semi-Arid Tropics (2016)
To assist farmers cope with climate change ICRISAT has been working on different approaches. The thrust, lessons learnt and the impact of five main models used for building climate-smart villages have been compiled as part of a feature in the ICRISAT Annual Report. Working for over 40 years in the semi-arid tropics, with varied partners, ICRISAT has developed climate resilient dryland crops and a pool of climate-smart technologies that are used in all of its climate-smart project interventions. Put together, the approaches focused on equipping farmers to use climate-smart scientific interventions and innovations, use climate information for cropping decisions, diversify livelihoods, link to markets, make agriculture profitable, rehabilitate and restore their environment and influence policy maker.